Multi-Resin Masked Stereolithography (MSLA) 3D Printing for Rapid and Inexpensive Prototyping of Microfluidic Chips with Integrated Functional Components - Isteaque Ahmed; Katherine Sullivan; Aashish Priye (Biosensors, 2022)
Stereolithography based 3D printing of microfluidics for prototyping has gained a lot of attention due to several advantages such as fast production, cost-effectiveness, and versatility over traditional photolithography-based microfabrication techniques. However, existing consumer focused SLA 3D printers struggle to fabricate functional microfluidic devices due to several challenges associated with micron-scale 3D printing. Here, we explore the origins and mechanism of the associated failure modes followed by presenting guidelines to overcome these challenges. The prescribed method works completely with existing consumer class inexpensive SLA printers without any modifications to reliably print PDMS cast microfluidic channels with channel sizes as low as ~75 μm and embedded channels with channel sizes as low ~200 μm. We developed a custom multi-resin formulation by incorporating Polyethylene glycol diacrylate (PEGDA) and Ethylene glycol polyether acrylate (EGPEA) as the monomer units to achieve micron sized printed features with tunable mechanical and optical properties. By incorporating multiple resins with different mechanical properties, we were able to achieve spatial control over the stiffness of the cured resin enabling us to incorporate both flexible and rigid components within a single 3D printed microfluidic chip. We demonstrate the utility of this technique by 3D printing an integrated pressure-actuated pneumatic valve (with flexible cured resin) in an otherwise rigid and clear microfluidic device that can be fabricated in a one-step process from a single CAD file. We also demonstrate the utility of this technique by integrating a fully functional finger-actuated microfluidic pump. The versatility and accessibility of the demonstrated fabrication method have the potential to reduce our reliance on expensive and time-consuming photolithographic techniques for microfluidic chip fabrication and thus drastically lowering our barrier to entry in microfluidics research.